(untitled) (Informatica, 2020)
The paper presents the results of our research in the field of applying algorithm visualizations within Data structures and algorithms subject. We accomplished several experiments relating the ability of students to solve simple problems in a pure visual way in one case and by programming the solution using a particular programming language in another one. The experiments are described and the results are analyzed within the paper. In accordance with our previous informal experiences and the results of the analysis we found there can be some part of students, which will be able to apply an algorithm to concrete problem in a visual way, but will not be able to express it clearly enough and implement it in given programming language. As an attempt to cope with the situation, we propose a new teaching approach, together with a prototype of study supporting system, based on the idea that students would participate on creating simple visualizations, not just using them. The purpose of such approach is to help students to develop both types of skills - understanding the algorithms and implementing them as well, by increasing the engagement level and supporting the active learning.